Higher visceral adiposity index was associated with an elevated prevalence of gallstones and an earlier age at first gallstone surgery in US adults: the results are based on a cross-sectional study - Zhang, Gaopeng; Ding, Zhe; Yang, Junping; Wang, Tianqi; Tong, Li; Cheng, Jian; Zhang, Chao (Frontiers in Endocrinology, 2023)
Objective: We sought to evaluate the association between visceral adiposity(VAI) index and the incidence of gallstones and the age at first gallstone surgery in adults in the United States. Methods: We selected individuals from the National Health and Nutrition Examination Survey (NHANES) database from 2017-2020 and evaluated the association between VAI and gallstone incidence and age at first gallstone surgery using logistic regression analysis, subgroup analysis, and dose-response curves. Results: A total of 7409 participants aged > 20 years were included in our study, 767 had a self-reported history of gallstone. After adjustment for all confounding factors, for each unit of VAI after Ln conversion, gallstone prevalence increased by 31% (OR = 1.31, 95% CI: 1. 17, 1.48), while the first gallstone surgery was 1.97 years earlier (β = -1.97, 95% CI: -3.35, -0.42), The dose-response curves showed a positive correlation between VAI and gallstone prevalence, There was a negative correlation between increased VAI and age at first gallstone surgery. Conclusions: A higher VAI is positively associated with the prevalence of gallstones and may lead to an earlier age at first gallstone surgery. This is worthy of attention, although causality cannot be established.